2021
DOI: 10.3390/healthcare9111502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Movement Function in Patients with Parkinson’s Disease: Network Meta-Analysis of Randomized Controlled Trials

Abstract: We aimed to compare the effectiveness of some different acupuncture modalities on motor function using the unified Parkinson disease rating scale (UPDRS)-III scores of idiopathic Parkinson’s disease (PD) via pairwise and network meta-analyses (NMA) of randomized controlled trials (RCTs). The Cochrane risk of bias assessment tool was used to assess the methodological quality of the included RCTs. A frequentist approach-based random effect model NMA was performed. Seventeen RCTs with 1071 participants were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…However, although the evidence had been inconclusive, the therapeutic potential of acupuncture in Parkinson’s disease seemed to be quite promising [ 41 , 42 ]. Thus, the present systematic review including renewed literature with recent RCTs, a large sample size and better-quality studies would be important to provide better evidence on the efficiency of acupuncture in Parkinson’s disease symptoms [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, although the evidence had been inconclusive, the therapeutic potential of acupuncture in Parkinson’s disease seemed to be quite promising [ 41 , 42 ]. Thus, the present systematic review including renewed literature with recent RCTs, a large sample size and better-quality studies would be important to provide better evidence on the efficiency of acupuncture in Parkinson’s disease symptoms [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies analysed in the present systematic review, which includes studies published between 2011 and 2021, there seems to be evidence for a positive effect of acupuncture on improving motor and non-motor symptoms in Parkinson’s disease. In all the studies reviewed, acupuncture was more effective in alleviating the symptoms of Parkinson’s disease than no treatment or conventional pharmacological treatment alone [ 43 ]. Additionally, some studies found that when acupuncture was used as an adjuvant to pharmacology, namely levodopa, it improved its therapeutic efficacy, allowing a reduction in the dose and the occurrence of adverse effects arising from its use [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the American Parkinson’s Association (APA), the management of Parkinson’s disease is a multi-disciplinary effort that involves not only pharmacological but also non-pharmacological interventions ( Cutson et al, 1995 ; Goldman and Guerra, 2020 ). Acupuncture is a common non-pharmacological treatment for improving gastrointestinal and neurological symptoms ( Kwon et al, 2021 ; Fan et al, 2022a ; Yao et al, 2022 ). Studies have shown that acupuncture can improve gastrointestinal and neurological symptoms while also relieving emotional symptoms ( Wang et al, 2022a ; Ying-Jia Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%